PENGARUH GREEN MARKETING DAN SOCIAL MEDIA MARKETING TERHADAP BRAND EQUITY DAN BRAND COMMITMENT PADA KONSUMEN STARBUCKS COFFEE DI KOTA PEKANBARU - Putri Salsabyla; Rahayu Danar Deny; Musfar Firli Tengku (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of Green Marketing and Social Media Marketingon Brand Equity and Brand Commitment to Starbucks Coffee consumers in PekanbaruCity. The population in this study were Starbucks Coffee consumers in Pekanbaru City.The data used in this study is primary data using a questionnaire. The number of samplestaken in the study were 100 samples and processed using the path analysis method withSPSS version 26 software. The results of this study indicate that: 1) Green Marketing hasa positive and significant influence on Brand Equity Starbucks Coffee in Pekanbaru City.2) Social Media Marketing has a positive and significant effect on Brand EquityStarbucks Coffee in Pekanbaru City. 3) Green Marketing has no influence on StarbucksCoffee's Brand Commitment in Pekanbaru City. 4) Social Media Marketing has no effecton Starbucks Coffee Brand Commitment in Pekanbaru City. 5) Brand Equity has apositive and significant effect on Brand Commitment Starbucks Coffee in Pekanbaru City.6) Green Marketing influences Brand Commitment through Starbucks Coffee BrandEquity in Pekanbaru City. consumers of Starbucks Coffee's eco-friendly marketing. 7)Social Media Marketing influences Brand Commitment through Starbucks Coffee BrandEquity in Pekanbaru City. Keywords: Green Marketing, Social Media Marketing, Brand Equity, BrandCommitment.